Lindley Generalized Inverted Exponential Distribution: Model and Applications (Pravaha, 2021)
In this article, we have proposed three parameters distribution using lindley family of distribution and Generalized inverted Exponential distribution called Lindley Generalized Inverted Exponential Distribution: Model and Applications(LGIE). The statistical properties as well as different characteristics like the hazard rate function (HRF), the probability density function (PDF), the cumulative distribution function (CDF), quantile function , skewness, and kurtosis of the proposed distribution are discussed. The parameters of the proposed distribution are estimated by using the maximum likelihood estimation (MLE), least-square estimation (LSE) and Cramer-Von-Mises (CVM) methods. All the computations are performed in R programming software. To assess the application of the proposed distribution, a real lifetime data set is analyzed and performed the goodness-of-fit.